2018
DOI: 10.1097/sla.0000000000002087
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Origin of Primary Colon Cancer Predicts Pathologic Response and Survival in Patients Undergoing Resection for Colon Cancer Liver Metastases

Abstract: Background To determine the prognostic value of embryonic origin in patients undergoing resection after chemotherapy for colon cancer liver metastases (CCLM). Methods We identified 725 patients with primary colon cancer and known RAS mutation status who underwent hepatic resection after preoperative chemotherapy for CCLM (1990-2015). Survival after resection of CCLM from midgut origin (n=238) and hindgut origin (n=487) was analyzed. Predictors of pathologic response and survival were determined. Prognostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 27 publications
4
84
1
Order By: Relevance
“…Similar with earlier analyses, demographic variables such age and gender were not associated with OS in the present study. Unlike recent reports which revealed that right sided colon tumors were associated with poorer OS after resection of CLMs (26,27), in the present analysis, the location of the primary did not significantly influence survival. Metastatic right sided tumors portend a more aggressive biology (than left-sided tumors), reflected mainly in more frequent hepatic and extrahepatic metastases and unresectable CLMs, but the influence of the primary tumor sidedness in patients with resectable CLMs was not proved in our series.…”
Section: Discussion Discussioncontrasting
confidence: 99%
“…Similar with earlier analyses, demographic variables such age and gender were not associated with OS in the present study. Unlike recent reports which revealed that right sided colon tumors were associated with poorer OS after resection of CLMs (26,27), in the present analysis, the location of the primary did not significantly influence survival. Metastatic right sided tumors portend a more aggressive biology (than left-sided tumors), reflected mainly in more frequent hepatic and extrahepatic metastases and unresectable CLMs, but the influence of the primary tumor sidedness in patients with resectable CLMs was not proved in our series.…”
Section: Discussion Discussioncontrasting
confidence: 99%
“… Flow diagram showing study selection process *Two cohorts were enrolled in the study from Yamashita et al …”
Section: Resultsmentioning
confidence: 99%
“…Adam et al 30 Umeda et al 31 Huang et al 32 Mavros et al 33 Viganò et al 34 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Norén et al 38 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Dupré et al 41 Liang et al 43 Rhu et al 44 Sultana et al 45 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 Engstrand et al 50 Goffredo et al 51 lmai et al 52 Koch et al 53 Laengle et al 54 Ledys et al 55 Liao et al 56 Lionti et al 57 Loosen et al 58 Makowiec et al 59 Margonis et al 60 Marques et al 24 Oshi et al 61 Palkovics et al 62 Shigematsu et al 63 Vallance et al 64 Wang et al 23 Wang et al 65 Zheng et al 66 Prediction interval 0·1 0 ·5 1 2 10…”
Section: Fig 2 Forest Plots Showing Impact Of Primary Tumour Locatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from T-status, N-status, and poor differentiation, which are two well-known prognostic factors (14,(17)(18)(19)(20), it is interesting to note that recently there was a countertendency about the location of the primary tumor. Historically, tumors in the rectum were thought to be the most aggressive (7,8,14), but recently some studies underlined how tumors in the right colon may be the most aggressive (21). Indeed, it has been shown that the embryonic origin of the colon cancer (midgut versus hindgut) may be associated with different pattern of response to preoperative therapies and consequentially to different rates of survival.…”
Section: Prognostic Factors Related To the Primary Colorectal Tumormentioning
confidence: 99%